Characterization of microbial communities from gut microbiota of hypercholesterolemic and control subjects - Morales, Cristian; Rojas, Gabriel; Rebolledo, Camilo; Rojas-Herrera, Marcelo; Arias-Carrasco, Raúl; Cuadros-Orellana, Sara; Maracaja-Coutinho, Vinicius; Saavedra, Kathleen; Leal, Pamela; Lanas, Fernando; Salazar, Luis A.; Saavedra, Nicolás (Frontiers in Cellular and Infection Microbiology, 2022)
In recent years, several studies have evidenced the importance of the microbiome to host physiology as metabolism regulator, along with its potential role in triggering various diseases. In this study, we analyzed the gut microbiota in hypercholesterolemic (cases) and normocholesterolemic (controls) individuals to identify characteristic microbial signature for each condition. Stool samples were obtained from 57 adult volunteers (27 hypercholesterolemic and 30 controls). The taxonomic profiling of microbial communities was performed using high-throughput sequencing of 16S rRNA V3-V4 amplicons, followed by data analysis using Quantitative Insights Into Microbial Ecology 2 (QIIME2) and linear discriminant analysis (LDA) effect size (LEfSe). Significant differences were observed in weight, height, body mass index (BMI) and serum levels of triglycerides, total cholesterol and low-density lipoprotein cholesterol (LDL-C) between the groups (p<0.05). LEfSe showed differentially abundant prokaryotic taxa (α=0.05, LDA score > 2.0) in the group of hypercholesterolemic individuals (Methanosphaera, Rothia, Chromatiales, Clostridiales, Bacillaceae and Coriobacteriaceae) and controls (Faecalibacterium, Victivallis and Selenomonas) at various taxonomic levels. In addition, through the application of Phylogenetic Investigation of Communities by Reconstruction of Unobserved States 2 (PICRUSt2), the predominance of pathways related to biosynthesis in hypercholesterolemic patients was established, compared to controls in which degradation pathways were predominant. Finally, in the analysis of co-occurrence networks, it was possible to identify associations between the microorganisms present in both studied groups. Our results point out to unique microbial signatures, which likely play a role on the cholesterol metabolism in the studied population.